Species relationships in the Neotropical genus Phareicranaus Roewer 1913 (Opiliones: Cranaidae): two new species and new data from Penial morphology - Pinto-Da-Rocha, Ricardo; Bonaldo, Alexandre B. (Zootaxa, 2011)
A reanalysis of the species relationships in the genus Phareicranaus Roewer, 1913, here considered the senior synonym of Acanthocranaus Roewer, 1913, Santinezia Roewer, 1923 and Comboyus Roewer, 1943, is carried out, using information unavailable in a previous analysis (of Santinezia). Subfamilies Cranainae and Prostygninae may be not monophyletic, since the generic relationships among cranaines are still obscure; it seems that Phareicranaus is closely related to Ventrivomer Roewer, 1913 and Ventrisudis Roewer, 1963, based on presence of a ventral apophysis on male coxa IV and cylindrical pedipalpal femur. The analysis performed with equal weighting generated 64 equally parsimonius trees (275 steps, ci= .24; ri= .60), and the strict consensus tree differs substantially from previous analyses. Based on results of the equally weigthed cladistic analysis, Phareicranaus is supported by the following unambiguous synapomorphies: penis base of the glans ringed; pedipalpal femur with a stout dorsoapical spine; strong ventral tubercles on pedipalpal femur and; area II invading area I (the two halves do not touch each other). Two new species are described, Phareicranaus divisor (type-locality: Brazil, Acre, Parque Nacional da Serra do Divisor) and P. patauateua (type-locality: Brazil, Pará, Ourém, Patauateua, fazenda Gavião). Male genitalia are described for the following cranaids: Chiriboga albituber Roewer, 1959; Metacranaus tricalcaris Roewer, 1913; Phareicranaus calcariger (Roewer, 1913), comb. n.; P. albimedialis (Goodnight & Goodnight, 1943); P. festae Roewer, 1925; P. parallelus Roewer, 1925; P. angelicus (Roewer, 1963) comb. n.; and P. ortizi (Roewer, 1952) and Ventrisudis mira Roewer, 1963. The following new combinations are proposed: from Acanthocranaus, Phareicranaus calcariger (Roewer, 1913); from Santinezia, Phareicranaus albilineatus (Roewer, 1932); P. angelicus (Roewer, 1963); P. arthrocentricus (Mello-Leitão, 1943), P. biordi (González-Sponga, 1991); P. calcarfemoralis (Roewer, 1917); P. calcaritibialis (Roewer, 1915); P. capayitaensis (González-Sponga, 2003); P. contrerasi (GonzálezSponga, 2003); P. circumlineatus (González-Sponga, 1989); P. curvipes (Roewer, 1916); P. duranti (González-Sponga, 1989); P. fronteriza (González-Sponga, 2003); P. furva (Pinto-da-Rocha & Kury, 2003); P. giganteus (Roewer, 1913); P. glaber (González-Sponga, 2003); P. gracilis (Pinto-da-Rocha & Kury, 2003); P. guaricoensis (González-Sponga, 2003); P. heliae (Avram, 1983); P. hermosa (Pinto-da-Rocha & Kury, 2003); P. lamitisus (González-Sponga, 2003); P. leonensis (González-Sponga, 2003); P. lucifer (Pinto-da-Rocha & Kury, 2003); P. manauara (Pinto-da-Rocha, 1994); P. noctiscansor (Townsend & Milne 2010); P. onorei (Pinto-da-Rocha & Kury, 2003); P. ortizi (Roewer, 1952); P. parvus (GonzálezSponga, 2003); P. sanarensis (González-Sponga, 2003); P. simonbolivari (Avram, 1987); P. singularis (H. Soares, 1970); P. soledadensis (González-Sponga, 2003); P. spinulatus (Goodnight & Goodnight, 1943); and P. subparamera (GonzálezSponga, 2003). Santinezia sanarensis humocaroensis González-Sponga, 2003, transferred to Phareicranaus, is elevated to species level, proposing the new combination and new status: Phareicranaus humocaroensis (González-Sponga, 2003). Three new names are proposed: Phareicranaus roeweri to replace Nieblia festae Roewer, 1925, preoccupied by Phareicranaus festae Roewer, 1925; Phareicranaus goodnightorum to replace Santinezia magna Goodnight & Goodnight 1942, preoccupied by Phareicranaus magnus (Roewer, 1932); and Phareicranaus kuryi to replace Comboyus albilineatus Roewer, 1943, preoccupied by Santinezia albilineata Roewer, 1932, which is presently a junior synonym of Inezia curvipes Roewer, 1916 (now Phareicranaus curvipes). Phareicranaus cingulatus Roewer, 1932 and Santinezia serratotibialis Roewer, 1932 are newly synonymized with Goniosoma calcariferum Simon, 1879 (the type species of Phareicranaus). Additionally, Phareicranaus giganteus Roewer, 1932 is newly synonymized with Holocranaus longipes Roewer 1913, and the monotypic genus Meridia Roewer 1913 (type species M. palpalis Roewer 1913) is transferred from Manaosbiidae to Cranaidae, Cranainae.